Pancasila as an Ethics of Social Media to Realize Digital Citizens - Yorman Yorman; Sadam Sadam (Journal of Social Studies Education, 2025)
Pancasila as the basis of the state and the outlook on life of the Indonesian nation has a central position in shaping the character and behavior of citizens. In the digital era marked by an unlimited flow of information, Pancasila values face serious challenges, especially in the ethical practice of social media. The phenomenon of ethical violations by the younger generation in the digital space reflects the weak understanding and internalization of Pancasila values. This research aims to identify digital citizenship development strategies based on Pancasila values in the context of 21st century education. The main goal is to formulate an educational model that is able to integrate digital literacy, digital ethics, and active and responsible participation in cyberspace. The research method used was a qualitative approach with a case study design, which involved participatory observation, in-depth interviews with educators and students, and analysis of education policy documents. The data was analyzed through thematic analysis techniques to explore patterns of understanding Pancasila values in the digital practice of young citizens. The results of this research are expected to make a theoretical and practical contribution in designing a democratic, ethical, and sustainable digital ecosystem. Thus, strengthening Pancasila values in the digital space is a strategic effort to maintain the integrity of the nation in the face of global disruption.